BCI, Personal Identity and Autonomy. Ulysses on the Ship of Theseus - Morente Parra, Vanesa (The Age of Human Rights Journal, 2025)
This article analyzes the ethical and legal challenges of Brain-Computer Interfaces (BCIs), focusing on their impact on personal identity and autonomy. It examines the transformative potential of neurotechnology, especially write-in BCIs that intervene directly in brain activity. Drawing from Ortega y Gasset’s zoon technikon and Parfit’s theory of personal identity, it reflects on how these systems may blur agency and self-continuity. The text also addresses the EU regulatory framework and the theory of neurorights. Using Ulysses on the Ship of Theseus as metaphor, it advocates preventive governance based on ethics, human rights, and informed, autonomous consent.